Cast Iron Reinforced with Foaming Ceramic Insert - Dulska, A.; Studnicki, A.; Cholewa, M.; Szajnar, J. (Archives of Foundry Engineering, 2018)
This paper presents matters related to production of ceramic and cast iron composite. The composite was made with the use of a foam structured ceramic insert. The tests included measuring of hardness, impact strength and resistance to abrasive wear of the composite produced. On the basis of obtaining results was stated that the use of foamed ceramic filters provides good conditions of filling a ceramic framework with molten grey or chromium cast iron. The growth of hardness of the ceramic- grey cast iron composite is ca. 60% as compared to the grey cast iron hardness. The growth of hardness of the ceramic- chromium cast iron composite is slight and does not exceed 5 % in comparison to the chromium cast iron. Introduction of the ceramic inserts deteriorates the cast iron impact strength by ca. 20 - 30 %. The use of ceramic inserts increases the resistance to abrasive wear in case of grey cast iron by ca. 13% and in case of the chromium cast iron by ca. 10 %.
Keywords: ceramics; Composite; cast iron